Knowledge, attitudes and practices of general practitioners in the Free State regarding the management of children with Attention Deficit Hyperactivity Disorder (ADHD) - A. Venter; G.P. van der Linde; G. Joubert (South African Family Practice)
The aim of this study,was to determine the knowledge, attitudes and practice of general practitioners (GP's) in the Free State regarding the management of children with Attention Deficit Hyperactivity Disorder (ADHD).